Methods of Developing Library Culture in Primary Class Students (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article talks about the culture of reading and methods of developing reading in elementary school students, the requirements and goals set for the pedagogue in this way. Literature has a special place among the arts. In fiction, life is reflected more fully than in other forms of art. Also, the life depicted in the fiction will be colorful and impressive. Therefore, it is possible to form the above feelings in students through the works of various genres given in primary school reading classes. Despite this, every child has his own world, his own ethics. Mobilizing the student to read books and works of art based on his interests and imagination requires a high level of skill and skill from the pedagogue. Artistic works of different genres have their own characteristics in terms of construction and style, and their impact on students is also different. Naturally, the text of each genre has its own linguistic features. For example, the text of poetic works is fundamentally different from the text of a story, the text of a fairy tale from the text of a poem, the text of a popular scientific article from the text of works belonging to the parable genre. If a riddle is mastered by comparing the similarities between objects and events, the content of proverbs requires interpretation by means of real life examples. Accordingly, when reading works of art of different genres, the teacher is required to choose appropriate methods. In each class, all the works read outside the classroom can be adapted to the students. It helps to develop the child's speech and increase vocabulary. Also, the attention of the students who watched the dramatized work increases, and their ability to store in their memory increases. Therefore, in today's article, we will present ideas on how to promote reading and how to convey them to students.